The fine art of success : how learning great art can create great business - Anderson, Jamie, 1971- (John Wiley & Sons, 2011)
You've read about Jack Welch, Lou Gerstner and Steve Jobs - but what can you learn about business from van Gogh and Picasso? The Fine Art of Success shows why you should look to pop-stars like Madonna or artists like Damian Hirst for guidance on innovation, competitive advantage, leadership, and a host of other business issues. Managers, marketing professionals, and students will see how these creative artists can help their organizations. Chapters include Madonna - Strategy at the dance floor; Damian Hirst - The shark is dead/How to build yourself a new market; Beuys - Understanding creativit.- Resumé vydavatel
Keywords: kreativita; podnikání; marketing; úspěch v podnikání; creative ability; business; success in business; elektronické knihy; sborníky; electronic books; papers of several authors